Effects of Topical Gabapentin on Ocular Pain and Tear Secretion - Cammalleri, Maurizio; Amato, Rosario; Olivieri, Melania; Pezzino, Salvatore; Bagnoli, Paola; Dal Monte, Massimo; Rusciano, Dario (Frontiers in Pharmacology, 2021)
Neuropathic ocular pain is a frequent occurrence in medium to severe dry eye syndrome (DES). Only palliative treatments, such as lubricants and anti-inflammatory drugs, are available to alleviate patients’ discomfort. Anesthetic drugs are not indicated, because they may interfere with the neural feedback between the cornea and the lacrimal gland, thus impairing tear production and lacrimation. Gabapentin (GBT) is a structural analog of gamma-amino butyric acid that has been used by systemic administration to provide pain relief in glaucomatous patients. We have already shown in a rabbit model system that its topic administration as eye drops has anti-inflammatory properties. We now present data on rabbits’ eyes showing that indeed GBT given topically as eye drops has analgesic and not anesthetic effects. Therefore, opposite to an anesthetic drug such as oxybuprocaine, GBT does not decrease lacrimation, but – unexpectedly – even stimulates it, via involvement of the autonomous nervous system and its mediators, and by induction of aquaporin 5 (AQP5) expression in the lacrimal gland. Moreover, data obtained in vitro on a primary human corneal epithelial cell line also show induction of AQP5 by GBT, suggesting that corneal cells might also contribute to the lacrimal stimulation promoted by GBT. In conclusion, GBT is endowed with analgesic, anti-inflammatory and secretagogue properties, all useful to treat neuropathic pain of the ocular surface, especially if derived from DES.